Putting to rest the claim to Sabah by the self-proclaimed Sultanate of Sulu - Abdul Gani Patail 1955- (Razak School of Government and Institut Terjemahan & Buku Malaysia, 2013)
The attempts by the self-proclaimed Sultanate of Sulu to lay claim to the State of Sabah in the Federation of Malaysia has been drawn into sharp focus through the armed intrusion and invasion of Malaysia's sovereign territory in the State of Sabah by persons claiming to be members of the Sultanate's alleged "Royal Sulu Sultanate Army" on 9 February 2013 and the subsequent armed attacks on Malaysian security personnel. This book aims to put to rest the claims made by the self-proclaimed Sultanate of Sulu through any of its self-styled "Sulu Sultans" by firstly establishing that the State of Sabah is a legitimate part of the Federation of Malaysia and secondly by rebutting the grounds of Sultanate's claim